A Multiband Printed Antenna Suitable for Wireless Applications - S. El Kilani; L. El Abdellaouib; J. Zbitou; J. Terhzaz; A. Errkik; M. Latrach (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This study deals with a new research work on a low cost multiband printed antenna which can be used for three operating frequency bands GSM900/PCS/WIFI/Bluetooth. The achieved antenna is mounted on an FR-4 substrate. In this study, the solts technique is used to obtain the multiband behavior. The different solts are inserted in the radiator face and the back face that is the ground. The whole circuit is optimized taking into account the good matching of the input impedance in the operating frequency bands with a stable radiation pattern. In order to optimize the proposed antenna structure we have used CST-MW and to compare the obtained simulation results we have conducted another electromagnetic simulation by using HFSS solver. The final circuit validated into simulation has been fabricated and tested which permits to validate the proposed multiband antenna.